Translator-computer interaction in action — an observational process study of computer-aided translation - Kristine Bundgaard; Tina Paulsen Christensen; Anne Schjoldager (JoSTrans: The Journal of Specialised Translation)
Though we lack empirically-based knowledge of the impact of computer-aided translation (CAT) tools on translation processes, it is generally agreed that all professional translators are now involved in some kind of translator-computer interaction (TCI), using O'Brien's (2012) term. Taking a TCI perspective, this paper investigates the relationship between machines and humans in the field of translation, analysing a CAT process in which machine-translation (MT) technology was integrated into a translation-memory (TM) suite. After a review of empirical research into the impact of CAT tools on translation processes, we report on an observational study of TCI processes in one particular instance of MT-assisted TM translation in a major Danish translation service provider (TSP). Results indicate that the CAT tool played a central role in the translation process. In fact, the study demonstrates that the translator's processes are both restrained and aided by the tool. As to the restraining influence, the study shows, for example, that the translator resists the influence of the tool by interrupting the usual segment-by-segment method encouraged by translation technology. As to the aiding influence, the study indicates that the tool helps the translator conform to project and customer requirements.